El trabajo colaborativo como estrategia didáctica en la unidad educativa “delia Ibarra de Velasco “de la provincia de Cotopaxi del cantón Pujili. - GUANOLUISA CURICHO, Orfa Elena (2019)
The project presented is the result of a research developed in an educational unit Delia Ibarra de Velasco, "in this sought to identify" The Collaborative Work as a methodological strategy "and how it affects the educational community. So it is a process that aims to introduce pedagogical strategies related to reasoning processes for the development of reflective thinking in school practices in basic education, where everyone is integrated, active within an institution. Collaborative work is seen as the process of identifying and responding to the diverse needs of all students through greater participation in the development of learning strategies in students, this would be a necessity to achieve comprehensive training by reducing work individual in collective participation. The general objective is to look for methodological strategies that help or improve the teaching-learning process, involving changes and modifications in content, approaches, structures and strategies, with technologies that help facilitate work and thus can meet all the objectives. The methodology used was the case study, to demonstrate and understand reality, for which multiplicity of evidence was collected through various techniques and instruments to give validity and reliability to the results obtained. One of the most outstanding results is the dialogue and the predominant interaction in the exchanges that take place in the pedagogical strategies of collaborative construction between the students and the teacher achieving processes of reflection, reasoning, argumentation, conceptualization or clarification of concepts, comments or contributions, which are characteristic of reflective thinking. "Collaborative work as a methodological strategy is part of a quality education that is reflected in teacher participation for teachers and all members of the educational community.